Impacts of climate change and vegetation response on future aridity in a Mediterranean catchment - Lorenzo Villani; Giulio Castelli; Estifanos Addisu Yimer; Celray James Chawanda; Albert Nkwasa; Bert Van Schaeybroeck; Daniele Penna; Ann van Griensven; Elena Bresci (Agricultural Water Management, 2024)
The climate in the Mediterranean region is expected to become warmer and drier but future projections of precipitation are uncertain, especially in the Northern part. Additionally, the difficulty in determining the plant physiological responses caused by CO2 rising complicates the estimation of future evaporative demand, increasing the uncertainty of future aridity assessments. Vegetation responses to rising CO2 are expected to increase radiation use efficiency and reduce stomatal conductance, hence increasing plant’s water use efficiency. These effects are often neglected when estimating future drought and aridity. Hence, the main objective of this study is to estimate the effect of climate change and vegetation stomatal conductance reduction on projected water balance components and the resulting impact on aridity in a medium-sized catchment of Central Italy. We validate and couple a hydrological model with climate projections from five regional climate models and perform simulations considering the vegetation responses or not. Results show that their inclusion significantly affects potential evapotranspiration. The other water balance components, namely actual evapotranspiration, water yield, percolation, and irrigation, are also influenced but with less significant changes. Considering or not the CO2 suppression effect on stomatal conductance, coupled with the uncertainty related to precipitation, highly affects the estimation of future aridity as the future climate classification ranges from “humid” to “semi-arid” depending on the simulation and climate model, even if model outputs need to be evaluated cautiously with CO2 concentration higher than 660 ppm.